Appendicitis and ganglioneuroma—an unusual co-existence. Issue 1 (22nd January 2022) - Koullouros, Michalis; Candler, Sarah; Smith, Caroline; Olakkengil, Santosh
Abstract: Ganglioneuromas are benign, fully differentiated mature tumours related to neuronal tissues and usually seen in the gastrointestinal tract, retroperitoneum and mediastinum. The few cases of appendiceal ganglioneuromas that were previously described in the literature belong to the paediatric population and were associated with genetic mutations and syndromes. We present a unique case of an Aboriginal Australian adult with acute appendicitis and concurrent ganglioneuroma diagnosed using histopathology and immunohistochemistry using Neu-N, S100 and Sox-10. The patient had no history of any of the syndromes associated with ganglioneuromatosis and had no other relevant family history.